African Childhood “Reawakened”: Using Cultural Studies Theory in Understanding the Use of Symbolism in Camara Laye’s The African Child. - Johnson, Ocan; Lillian, Tindyebwa (East African Journal of Traditions, Culture and Religion, 2021)
This paper reports the findings of a pragmatic study that uses follow-up interviews as a method to investigate how participants read the language in the novel by a renowned African novelist Camara Laye. The study builds on antecedent work that has identified patterns of language presentation as techniques of characterisation in the novel “The African Child”. The article offers a spotlight on the critical use of symbolism in the novel ‘The African child’ (Laye, 1953). This article is set in a research context that brings together surveillance from cultural studies theory on the use of symbols in the novel. The results show that symbols are read significantly faster than the overall clusters which are stored as units in the brain. This pronouncement is complemented by the results of the follow-up questions which indicate that readers do not seem to refer to symbols when talking about character information, although they are able to refer to symbols when prompts are used to elicit information. Beyond the specific results of the study, this article makes a contribution to the development of complementary methods in children’s literature from Africa and it points to directions for further sub-classifications of the use of symbolism in children’s literature that could not be achieved on the basis of this data alone.